MEMBANGUN MODEL PERLINDUNGAN HUKUM TERHADAP MASYARAKAT SEBAGAI KORBAN PENCEMARAN DAN/ATAU PERUSAKAN LINGKUNGAN OLEH KORPORASI DENGAN PRINSIP RESTORATIVE JUSTICE - Yeni Widowaty; Fadia Fitriyanti (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Due to pollution and environmental destruction that most feel is the victim. Most victims also suffered losses, both material and immaterial losses, therefore it is natural that the victims should receive protection. The purpose of this research is to analyze about: 1) the resolution of environmental cases which occur either through the courts or out of court; 2) the implementation of legal protection for the victims of pollution and environmental destruction; 3) formulating the ideal model of legal protection for the victims of pollution and environmental destruction by the corporation is based on the principles of restorative justice in the future. The research method is used the socio-legal research using primary and secondary data. The results showed that environmental cases can be resolved through the court and outside the court. Ideal model of legal protection for the victims of pollution and / or environmental destruction by the corporation is based on the restorative justice principle in the future.The offender in this case as the corporation will deal with victims of environmental pollution and the state as a facilitator. The Facilitator from the state for this early stage could be represented by a judge. In an agreement between the perpetrator and the victim of the most important is the provision of compensation from the offender to the victim. Ideally in the concept forward on major and compensation mechanism is stipulated in the rules of implementation.